Infant vitamin d supplementation and allergic conditions in adulthood: northern Finland birth cohort 1966 - Hyppönen, E; Sovio, U; Wjst, M; Patel, S; Pekkanen, J; Hartikainen, AL; Jarvelinb, MR (2004)
Allergen-induced secretion of Th2-type cytokines and IgE production have recently been reported to be increased in mice treated with 1,25(OH)(2)D, the active form of vitamin D. Our objective was to investigate whether vitamin D supplementation in infancy is associated with the risk of atopy, allergic rhinitis, and asthma. The Northern Finland Birth Cohort consists of all individuals in the two most northern provinces of Finland who were due to be born in 1966. Data on vitamin D supplementation during the first year of life was obtained in 1967. Current asthma and allergic rhinitis were reported at age 31 years (n = 7,648), and atopy determined by skin-prick test in a sub-sample still living in northern Finland or the Helsinki area (n = 5,007). The prevalence of atopy and allergic rhinitis at age 31 years was higher in participants who had received vitamin D supplementation regularly during the first year compared to others (OR 1.46, 95%CI 1.4-2.0, and OR 1.66, 95%CI 1.1-1.6, respectively). A similar association was observed for asthma (OR 1.35, 95%CI 0.99-1.8). These associations persisted after adjustment for a wide range of behavioral and social factors (adjusted: OR 1.33 for all, P = 0.01 for atopy, P = 0.001 for allergic rhinitis, and P = 0.08 for asthma). We observed an association between vitamin D supplementation in infancy and an increased risk of atopy and allergic rhinitis later in life. Further study is required to determine whether these observations reflect long-term effects on immune regulation or differences in unmeasured determinants of vitamin D supplementation